Mandatory and voluntary information disclosure and the effects on financial analysts: Evidence from China. Issue 3 (3rd August 2015) - Wang, Shengnian; Han, Liang; Gao, Weiting
Abstract : Purpose: – This paper aims to make a comparison, different from existing literature solely focusing on voluntary earnings forecasts and ex post earnings surprise, between the effects of mandatory earnings surprise warnings and voluntary information disclosure issued by management teams on financial analysts in terms of the number of followings and the accuracy of earnings forecasts. Design/methodology/approach: – This paper uses panel data analysis with fixed effects on data collected from Chinese public firms between 2006 and 2010. It uses an exogenous regulation enforcement to minimise the endogeneity problem. Findings: – This paper finds that financial analysts are less likely to follow firms which mandatorily issue earnings surprise warnings ex ante than those voluntarily issue earnings forecasts. Moreover, ex post, they issue less accurate and more dispersed forecasts on former firms. The results support Brown et al. 's (2009) finding in the USA and suggest that the earnings surprise warnings affect information asymmetries. Practical implications: – This paper justifies the mandatory earnings surprise warnings policy issued by Chinese Securities Regulatory Commission in 2006. Originality/value: – Mandatory earnings surprise is a unique practical regulation for publicly listed firms in China. This paper, for the first time, provides empirical evaluation on the effectiveness of a mandatory information disclosure policy in China. Consistent with existing literature on information disclosure by public firms in other countries, this paper finds that, in China, voluntary information disclosure captures more private information than mandatory information disclosure on corporate earnings ability.